Materials for a critique of the present: Marxism and religion in Franz Hinkelammert - RAMAGLIA, Juan Manuel; SÁNCHEZ, Esteban Gabriel (Utopía y Praxis Latinoamericana, 2022)
In Franz Hinkelammert’s work the critique of modernity assumes the critical potential of theology in connection with the Marxist tradition. A fundamental thesis of the author is his criticism of the idolatrous character of capitalism. This criticism involves recognizing the mythical elements that operate within modern consciousness and its instrumental rationality. It is about a matter of replacing the materials for a critique of the present that allows us to venture into the mythical labyrinth of modernity, recovering an actively humanist vision and an ethical-critical conscience in Hinkelammertian thinking.